Gender in crop improvement and other technology development - Bioversity International; International Center for Tropical Agriculture (2024)
The "9 Briefs Series" by the Alliance of Bioversity International and CIAT explores critical dimensions of gender, youth, and social inclusion within food, land, and water systems.